Impacts of carob pulp (Ceratonia siliqua L.) and vitamin E on pork colour, oxidative stability, lipid composition and microbial growth - Bottegal, Diego Nicolas; Latorre, María Ángeles; Lobón Ascaso, Sandra; Argemí Armengol, Immaculada; Álvarez-Rodríguez, Javier (Elsevier, 2025)
This study aimed to evaluate the impact of the dietary by-product rich in polyphenols (Carob pulp, Cp) and supra-nutritional level of vitamin (Vit) E on pork quality and shelf-life of meat stored in modified atmosphere packaging for 15 days. A total of 44 pigs (entire males and gilts, 170 ± 4.5 days of age and 127.8 ± 3.6 kg of body weight) were randomly selected from a larger group (one pig per pen). Pigs were fed ad libitum with one of four diets in a 2 × 2 factorial arrangement, with two feed inclusion levels each for Cp (0 vs. 20 %) and Vit E (30 (Low) vs. 300 IU/kg of feed (High)) for 40 days. No interactions between Cp and Vit E were detected for most variables assessed. Meat colour attributes evolved regardless of diet or sex, although metmyoglobin formation was preserved until 13 days. The Cp diets did not affect malondialdehyde nor α-tocopherol content in meat. High Vit E limited the malondialdehyde production up to 13 days and increased 1.8-fold the muscle α-tocopherol content compared to Low Vit E. The 20 %-Cp group tended to reduce total aerobic microbial count compared to 0 %-Cp group after 15 days of storage. Including Cp slightly affected the meat fatty acid (FA) profile, whereas Vit E did not modify it. Entire males presented higher content of polyunsaturated FA than gilts. Including 20 % Cp into pigs' diets does not impair meat quality, while High Vit E reduces lipid oxidation but not meat discolouration.